Analisis Pengaruh Citra Merek, Celebrity Endorser, dan Online Consumer Review Terhadap Keputusan Pembelian (Studi pada Konsumen Scarlett Whitening di Kota Semarang) - Resti Rahmadani; Sri Rahayu Tri Astuti (Faculty of Economics and Business Diponegoro University, 2023)
ABSTRACT This study aims to examine the effect of brand image, celebrity endorser, and online consumer reviews on purchasing decisions among consumers of scarlett whitening products in the city of Semarang. The variables used in this study are brand image, celebrity endorser, and online consumer reviews as the independent variables and purchasing decisions as the dependent variable. The sample used in this study was 130 people living in Semarang who had purchased scarlett whitening products. In this study the sample collection technique used was non probability sampling with purposive sampling technique using a questionnaire for data collection method. The analysis used is Multiple Linear Analysis using the SPSS 25 analysis tool. The results in this study indicate that brand image, celebrity endorser, and online consumer reviews have a positive influence on purchasing decisions on scarlett whitening products.